High pressure phase transition and strength estimate in polycrystalline alumina during laser-driven shock compression - Hari, A; Hari, R; Heighway, PG; Smith, RF; Duffy, TS; Sims, M; Singh, S; Fratanduono, DE; Bolme, CA; Gleason, AE; Coppari, F; Lee, HJ; et al. (IOP Publishing, 2022)
Alumina (Al2O3) is an important ceramic material notable for its compressive strength and hardness. It represents one of the major oxide components of the Earth's mantle. Static compression experiments have reported evidence for phase transformations from the trigonal α-corundum phase to the orthorhombic Rh2O3(II)-type structure at ∼90 GPa, and then to the post-perovskite structure at ∼130 GPa, but these phases have yet to be directly observed under shock compression. In this work, we describe laser-driven shock compression experiments on polycrystalline alumina conducted at the Matter in Extreme Conditions endstation of the Linac Coherent Light Source. Ultrafast x-ray pulses (50 fs, 1012 photons/pulse) were used to probe the atomic-level response at different times during shock propagation and subsequent pressure release. At 107 ± 8 GPa on the Hugoniot, we observe diffraction peaks that match the orthorhombic Rh2O3(II) phase with a density of 5.16 ± 0.03 g cm−3. Upon unloading, the material transforms back to the α-corundum structure. Upon release to ambient pressure, densities are lower than predicted assuming isentropic release, indicating additional lattice expansion due to plastic work heating. Using temperature values calculated from density measurements, we provide an estimate of alumina's strength on release from shock compression.